PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS INKLUSIF (INCLUSSIVE LEARNING) PADA MATERI KLASIFIKAIH MAKHLUK HIDUP KELAS VII SMP - Hadi Jaya Putra, Sukarman; Yanseli, Martha; Yoseph Tuta Mago, Oktavius (Universitas Cokroaminoto Palopo, 2024)
The purpose of this study is to develop an inclusive-based Student Worksheet (LKPD) on the classification of living organisms for Grade VII SMP students that can support effective learning for students with various abilities. The background of this research stems from the challenge of creating learning media that can accommodate the needs of students with diverse abilities and backgrounds, especially in complex biological concepts. This study was conducted at SMPK St. Mikael Brai, involving Grade VII students from varying levels of learning abilities. The method used is a Research and Development (R&D) model with the following steps: needs analysis, product design, expert validation, small and large-scale trials, and product revision. Data was collected through observations, questionnaires, and interviews involving both teachers and students. The results showed that the developed LKPD received excellent validation, with an average score of 96.86% from material, language, and media experts. The feasibility trials in the classroom, with a score of 95% for students and 93% for teachers, demonstrated that this LKPD is effective in enhancing students' understanding of the classification of living organisms and stimulating active student engagement in the learning process. This study contributes to the development of inclusive-based learning media that can be used to facilitate a fair and equitable learning process for all students.